The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1365-2125.2000.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pharmacokinetics and electrocardiographic pharmacodynamics of loratadine with concomitant administration of ketoconazole or cimetidine

Abstract: Aims To evaluate whether ketoconazole or cimetidine alter the pharmacokinetics of loratadine, or its major metabolite, desloratadine (DCL), or alter the effects of loratadine or DCL on electrocardiographic repolarization in healthy adult volunteers. Methods Two randomized, evaluator-blind, multiple-dose, three-way crossover drug interaction studies were performed. In each study, subjects received three 10 day treatments in random sequence, separated by a 14 day washout period. The treatments were loratadine al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…The enhanced bioavailability of loratidine may have been due to inhibition of both CYP 3A4-mediated metabolism and P-gp in the intestine and/or liver by the presence of hydrocortisone. This result was consistent with previous studies showing that single oral administration of cimetidine, clarithromycin or ketoconazole significantly increased the AUC and Cmax of loratadine in rats by inhibition of CYP3A4 (Carr et al, 1998;Kosoglou et al, 2000). Overall, the presence of hydrocortisone significantly enhances the oral bioavailability of loratadine by increasing the intestinal absorption and reducing the first-pass metabolism of loratadine.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The enhanced bioavailability of loratidine may have been due to inhibition of both CYP 3A4-mediated metabolism and P-gp in the intestine and/or liver by the presence of hydrocortisone. This result was consistent with previous studies showing that single oral administration of cimetidine, clarithromycin or ketoconazole significantly increased the AUC and Cmax of loratadine in rats by inhibition of CYP3A4 (Carr et al, 1998;Kosoglou et al, 2000). Overall, the presence of hydrocortisone significantly enhances the oral bioavailability of loratadine by increasing the intestinal absorption and reducing the first-pass metabolism of loratadine.…”
Section: Resultssupporting
confidence: 82%
“…Previous reports have indicated pharmacokinetic interactions between loratadine and other drugs, such as cimetidine, clarithromycin and ketoconazole (Carr et al, 1998;Kosoglou et al, 2000). These significantly increased the AUC and Cmax of loratadine in rats by inhibition of CYP3A4 and P-gp.…”
Section: Introductionmentioning
confidence: 82%
“…The enhanced oral bioavailability of loratadine contributed to the competitive inhibition of loratadine metabolism by CYP 3A4 both in the liver and intestine. This result was consistent with previous studies showing that a single oral administration of cimeti- www.biomolther.org dine, clarithromycin and ketoconazole signifi cantly increased the AUC and C max of loratadine in rats through inhibition of CYP3A4 (Carr et al, 1998;Kosoglou et al, 2000). These results are coincident with previous studies, in which CYP3A9 expressed in rat is corresponds to the ortholog of CYP3A4 in human (Kelly et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies showed that CYP3A4 inhibitors such as clarithromycin (Carr et al, 1998), erythromycin (Brannan et al, 1995), and ketoconazole (Kosoglou et al, 2000) significantly increased the plasma concentrations of loratadine. These data indirectly suggested a significant in vivo involvement of CYP3A4 in loratadine metabolism.…”
Section: Discussionmentioning
confidence: 99%